Zaja Bandida Hutagtyn Hürėėnij huvilgaan, Güž lam Batsuurʹ (1895-1925) - Mjagmarsambuu, Galindėvijn 1964-; Batdorž, Čagdarsümbėrėlijn ("Soëmbo printing" HHK, 2018)
On the life and times of Gu̇zh lam Batsuurʹ (1895-1925)..